2016
DOI: 10.1037/npe0000051
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation influence: Differential neural responses of consumers during shopping online.

Abstract: In diverse social environments, recommendations from others have the power to change consumer behavior. In this study, we explore the influence of recommendations made by others with whom consumers have different degrees of familiarity on the cognitive processes of online shopping using event-related potentials (ERPs). Sixteen healthy university subjects were recruited for 2 experiment tasks. These subjects viewed a stimulus sequence of pictures of certain products that contained either recommendations from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Actually, the processing of an unfamiliar brand data takes more time, and during this time, the brain leans towards the familiar brands that has already been exposed to and chooses that [21]. This delay in data processing for an unfamiliar brand can be in agreement with the studies on the effect of the social environment and attributes as well as the reward system in choosing the familiar brands [4,21].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Actually, the processing of an unfamiliar brand data takes more time, and during this time, the brain leans towards the familiar brands that has already been exposed to and chooses that [21]. This delay in data processing for an unfamiliar brand can be in agreement with the studies on the effect of the social environment and attributes as well as the reward system in choosing the familiar brands [4,21].…”
Section: Discussionsupporting
confidence: 69%
“…Actually, it can be said that preference of a familiar brand occurs through social reward [21], as the advertisements for these brands use the people' feelings and lifestyles. This is while an early preference (observed in the N1 component) might be caused by positive and pleasant emotions, and in fact, followed by quick activation of the individual's reward system for repeated and faster choice of the brand [4,21,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (2009), as evidenced by an enhanced prolonged P300, physiologically demonstrated herding behavior observed in online purchases based on consistent book recommendations. An enhanced N200 associated with familiar sources (vs unfamiliar sources), also verified the role of trust in online book recommendations (Guo et al , 2016).…”
Section: Advantages Of An Electroencephalogram Approach To Consumer Researchmentioning
confidence: 61%
“…Other studies have investigated the roles of the social environment, social attributes and the reward system in choosing familiar brands 57 , 58 . Thus, future work should investigate brain activation patterns using the SNN model in terms of psychosocial factors, personality variables and inter-individual differences that may affect a person’s cognitive response to familiar logos and, indeed, brand preference.…”
Section: Discussionmentioning
confidence: 99%